A cognitive account of expertise: Why Rational Choice Theory is (often) a fiction. (February 2014) - Muntanyola-Saura, Dafne
This paper arises from the need to explain expert decision-making in professional environments from a plural and interdisciplinary perspective. An extended review of Rational Choice Theory (RCT) from its first developments to current trends makes explicit the mismatch between RCT and empirical work settings. A review of recent theories on the cognitive abilities of agents makes clear the lack of integration between findings in evolutionary psychology, cognitive science, perceptual psychology and neurology, and those proposed by RCT. We will examine the causes for the failure of Good Old Fashioned Artificial Intelligence (GOFAI), the strongest empirical program for testing RCT premises. Contributions from the cognitive and social sciences put forward the weaknesses of analytical sociology at all four levels: the biological, the psychological, the epistemological, and the ontological. Alternative explanations from contemporary cognitive science will be put forward.